2003
DOI: 10.1046/j.1365-2516.2003.00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term FEIBA prophylaxis does not prevent progression of existing joint disease

Abstract: Activated prothrombin complex concentrates have been used to treat bleeding episodes for patients who have developed an inhibitor to factor VIII (FVIII). FEIBA-Vh (FVIII bypassing activity, FEIBA) has been used since 1970 for this purpose and with FVIII for immune tolerance programmes. Studies have not been presented to show the safety and efficacy of FEIBA when given over a long period of time to prevent haemophilic arthropathy with bleeding into the joints of these patients. This study was undertaken to asce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
95
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 12 publications
(15 reference statements)
6
95
1
1
Order By: Relevance
“…Treatment duration across these studies varied from a few months to several years. Consistent with the current case report, two of the previous studies also found decreased inhibitor titers during FEIBA prophylaxis [8,10]. Notably, studies by Escuriola-Ettingshausen et al [9], Valentino and Salit [12], and Leissinger [7] also showed maintenance or improvement of existing arthropathy.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Treatment duration across these studies varied from a few months to several years. Consistent with the current case report, two of the previous studies also found decreased inhibitor titers during FEIBA prophylaxis [8,10]. Notably, studies by Escuriola-Ettingshausen et al [9], Valentino and Salit [12], and Leissinger [7] also showed maintenance or improvement of existing arthropathy.…”
Section: Discussionsupporting
confidence: 91%
“…While this case represents a novel experience in the treatment of inhibitor-positive patients in Japan, the findings are consistent with data from other patients treated prophylactically with FEIBA [6,[8][9][10][11][12], which reported low or decreased (relative to pretreatment) bleeding episode frequencies for patients treated with a variety of FEIBA regimens, including 50-100 U three or four times per week, or 50 or 100 U/kg/day. Treatment duration across these studies varied from a few months to several years.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although anecdotal reports [13][14][15][16] have suggested that regular administration of AICC may prevent bleeding in patients with hemophilia A and factor VIII inhibitors, the efficacy of this therapeutic regimen has been unproved. The Prophylaxis with Factor Eight Inhibitor Bypassing Activity (Pro-FEIBA) study was designed to compare the efficacy and safety of AICC prophylaxis with ondemand therapy in this patient population.…”
Section: Discussionmentioning
confidence: 99%